Comparison of mini-open, anteroinferior psoas approach and mini-open, direct lateral transpsoas approach for lumbar burst fractures: A retrospective cohort study - Pan, Bin; Yu, Weiyang; Lou, Chao; Gao, Jiawei; Huang, Wenjun; He, Dengwei (Frontiers in Surgery, 2022)
Objective: We evaluated the effect of a novel modified OLIF technique (anteroinferior psoas approach, AIPA) for anterior decompression reconstruction in lumbar burst fractures, and compared the clinical, radiological outcomes and approach-related complications with the mini-open, lateral transpsoas approach (LTPA). Methods: From March 2016 to November 2019, 68 patients with lumbar burst fractures underwent one-stage monosegmental posterior/anterior surgery from L1–L4 segments. 35 patients included in AIPA and 33 patients in LTPA group underwent anterior decompression reconstruction. The clinical, radiological and functional evaluation outcomes were recorded during the 16-60 months follow-up period. Results: At the latest follow up, neurological state of one or more ASIA grades were achieved in AIPA (90.9%) and LTPA group (94.9%). No significant differences were noted between the two groups regarding preoperative and postoperative Cobbs angle. The surgery time (192.29 vs 230.47 min, P = 0.02) in AIPA group was better compared with LTPA. The AIPA showed better improvement on Oswestry Disability Index (43.4% vs 60.8%, P < 0.05) and Mental Component Score (49.0% vs 43.7%, P < 0.05) one month after surgery, but no difference at the latest follow-up. 10 patients (9 in LTPA and 1 in AIPA) experienced temporary motor deficits in hip flexor and groin or thigh numbness, which disappeared six months after surgery. Conclusions: Compared with lateral transpsoas approach, anterior decompression reconstruction via mini-open, anteroinferior psoas approach was a safe and less invasive approach, with fewer approach-related complications in the treatment for unstable lumbar burst fractures.